Pengaruh Kualitas Laba Dalam Memoderasi Hubungan Kepemilikan Kas dan Efisiensi Perusahaan (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2016) - Dina Kaltsum; Nurzi Sebrina (Universitas Negeri Padang, 2019)
This study aims to examine the effect of earnings quality in moderating the relationship of cash holdings and firms efficiency. This study is classified as causative research. The population in this study are manufacturing companies listed on the Indonesian Stock Exchange period of 2013 to 2016. By using purposive sampling method, there were 88 companies as the research’s sample. Firms Efficiency variable are measured by the DEA model, cash holdings variable are measured by cash ratio, and earnings quality variable are measure by accrual quality. The type of data used is secondary data obtained from www.idx.co.id and used is panel regression analysis. The results of this study indicate that cash holdings has a positive and significant effect on firms efficiency, but earnings quality is not able to strengthen or weaken the relationship between cash holdings and firms efficiency. Keywords: Cash holdings, earnings quality, firms Efficiency.